ECO-INNOVATIONS IN JAPAN: THE MAIN DIRECTIONS - A. I. Bancheva (Vestnik MGIMO-Universiteta)
The paper presents the main aspects of the environmental technologies sector nowadays in Japan. Basing on the governmental definition of «ecological innovations», eco-innovations are developed according to the traditional Japanese concept of value creation – «monozukuri». Ecological innovations include technological improvements as well as social reforms. So far the paper draws an attention on two types of innovations: engineering technologies and social reforms (programms, education etc.). Basing on governmental Programs and open data bases the most important environmental technologies for nowadays in Japan are defined. From author’s point of view the first vector for Japan is «green energy» (alternative energy, energy efficiency) – innovations concern the challenge of climate change. Regarding this issue the aspects and technologies from «The Cool Earth Innovative Energy Technology Program» are described. The second vector is eco-innovations for pollution control and waste utilization – the traditional sector for Japan from 1970s. And the third one is defined as information and communication technologies for environmental challenges («green ICT») – the new vector for Japan as well as for the other countries. In the paper the issues of research and development activities, financial issues eco-innovations’ management and transfer are considered. The role of Japan Science and Technology Agency (JST) and National Institute of Science and Technology Policy (NISTEP) is discussed. The significant issue of verification of new technologies realized by Ministry of Environment in Japan is mentioned.